Chronic exertional compartment syndrome of the leg in athletes: Evaluation and management - Gill, C. S.; Halstead, M. E.; Matava, M. J. (The Physician and Sportsmedicine, 2010)
Abstract: Chronic exertional compartment syndrome (CECS) is a well-known cause of activity-related lower leg pain in both athletes and nonathletes. In contrast to acute compartment syndrome, CECS is generally not related to trauma, and is often suspected in the outpatient setting by primary care physicians, podiatrists, sports medicine clinicians, and orthopedic surgeons. The diagnosis of CECS is often overlooked because patients avoid or withdraw from exacerbating physical activities instead of seeking treatment for their symptoms from a health care professional. A thorough history and physical examination of an individual with activity-related lower leg pain is necessary for correct diagnosis to occur. Appropriate diagnostic testing with measurement of intracompartmental pressures reliably confirms the diagnosis of CECS. Nonoperative treatments of CECS rarely leads to complete resolution of symptoms or an individual`s ability to return to previous levels of recreational or athletic activity. Fasciotomy of the involved compartments can reliably lead to resolution of pain and the ability to return to previous activities within 6 weeks.